The Arctic & Antarctica: Echo Chamber, Pedro Cera, Lisbon, Portugal, April 12th - May 19th 2018. - Neudecker, Mariele (BathSPAdata, 2021)
Two pivotal research trips to Greenland in 2012 and 2015 extended Neudecker’s ongoing research into how the legacy of the Romantic Sublime and limited visual representations shape our perceptions of the Arctic regions . Questioning notions of wilderness in the context of current environmental and geopolitical realities this collection generates new perspectives on the Contemporary Sublime. This item contains an exhibition press release and 6 exhibition views. This item documents the inclusion of 3 of Neudecker's Arctic/Antarctica works as part of her solo survey exhibition, Echo Chamber at Pedro Cera in Lisbon, Portugal in 2018. The first was a tank work Some Things Happen All At Once 2014 which was based on the Halley Vl Antarctica Research Station, and made for ANTARCTOPIA , an exhibition in the Antarctica Pavilion, at the 2014 Venice Architecture Biennale. Secondly, On the Other Side 2016 a wall hung, stainless steel stereoscopic viewer and image. Less Far and Further 2018 was another tank piece made for this exhibition Photography: Courtesy of Pedro Cera Gallery, Lisbon, Portugal. Used with permission. The work is under copyright and may not be used without permission. Use of this repository acknowledges cooperation with its policies and relevant copyright law.